1980
DOI: 10.3109/03093648009164567
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of reamputation and death after gangrene of the lower extremity

Abstract: Since 1972 the Danish Amputation Register (DAR) has recorded major amputations in Denmark. The register is based on voluntary detailed reports from surgical and orthopaedic departments. The present investigation is based upon 2029 amputations for arteriosclerotic and diabetic gangrene with an observation period up to 4 years. The incidence of ipsilateral reamputation is high in the immediate postoperative period with 10-4% after one month, 16-5% after three months and 18-8% after six months. Later the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(47 citation statements)
references
References 11 publications
1
41
1
1
Order By: Relevance
“…In the current study, mean time to revision was 244 days. These results are analogous to those of Ebskov and Josephsen, 16 who reported that the majority of ipsilateral reamputations occurred within the first year. Kanade et al 17 reported that the second ipsilateral amputations in their study population oc- curred after an average of 21 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, mean time to revision was 244 days. These results are analogous to those of Ebskov and Josephsen, 16 who reported that the majority of ipsilateral reamputations occurred within the first year. Kanade et al 17 reported that the second ipsilateral amputations in their study population oc- curred after an average of 21 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…At 48 months following amputation this figure had increased only another 4% to 23 %. 18 Descriptive studies have reported that approximately 6-30% of amputees will undergo second leg amputations within 1 to 3 years of their initial amputation. 18 · 36 · 37 · 39 Table 4 reports the frequency of second leg amputations among initial amputation survivors.…”
Section: Original Articlesmentioning
confidence: 99%
“…They are frequent causes of lower extremity amputations in diabetics. Once the loss of one limb has occurred, the prognosis of the contralat-era1 one is poor (35). Measures to prevent foot ulcers and amputations entail patient education, frequent examinations of the feet, wearing of well-fitting shoes, use of heel booties in bed-ridden patients and regular visits to a podiatrist.…”
Section: Foot Ulcers and Peripheral Vascular Diseasementioning
confidence: 99%